Economic Development of Digital Business Technology in Indonesia - Detha Prasetio Kumara (Penerbit Hellow Pustaka, 2023)
Information and Communication Technology (ICT) has become a necessity in this day and age, many people in Indonesia have used it in their daily lives. The dynamics of the economy cannot be separated from the development and advancement of technology, infrastructure, productivity and innovation. Scientific progress has an impact on technological progress. Disruptive innovation creates its own market that continues in the digital business sector (E commerce). Technological developments are also accompanied by the development of ways to convey information in communication so that activities become faster by using the internet with social media applications. This study aims to descriptive analysis of the development of E-Commerce through and estimate the influence of E-Commerce sector business on Indonesia's economic growth. Technological developments have brought rapid changes and intense competition. Human mobility, the distribution of goods, as well as the traffic of capital and information are rapidly developing through digitization. Changes in individual activities began to affect the transaction process they do, each individual does not depend anymore on traditional money but sudan uses virtual money and in the future all will be connected in this direction.